2023
DOI: 10.3389/fphar.2023.1230783
|View full text |Cite
|
Sign up to set email alerts
|

Integrative evidence construction for resveratrol treatment of nonalcoholic fatty liver disease: preclinical and clinical meta-analyses

Xuan He,
Yubing Li,
Xinyu Deng
et al.

Abstract: Background: Resveratrol, a polyphenol found in various plants, is known for its diverse bioactivities and has been explored in relation to nonalcoholic fatty liver disease (NAFLD). However, no high-quality evidence exists regarding its efficacy.Objective: a meta-analysis was conducted to evaluate the potential efficacy of resveratrol in treating nonalcoholic fatty liver disease by analyzing both preclinical studies and clinical trials.Method: PubMed, Embase and Web of Science were searched for the included lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Resveratrol effectively decreases the levels of fatty liver biomarkers and confers protection against MASLD in animal studies. Nonetheless, further studies are needed to determine its clinical applicability [ 148 ]. Breviscapine directly inhibits the TGF-β-activated kinase 1 (TAK1) and is deemed a possible candidate for the treatment of MASH [ 149 ].…”
Section: Research Prospects For Therapeutic Strategiesmentioning
confidence: 99%
“…Resveratrol effectively decreases the levels of fatty liver biomarkers and confers protection against MASLD in animal studies. Nonetheless, further studies are needed to determine its clinical applicability [ 148 ]. Breviscapine directly inhibits the TGF-β-activated kinase 1 (TAK1) and is deemed a possible candidate for the treatment of MASH [ 149 ].…”
Section: Research Prospects For Therapeutic Strategiesmentioning
confidence: 99%
“…In clinical investigations, the implication of resveratrol and GLP-1 (Glucagon-like peptide-1) receptor agonists, both of which can activate SIRT1, in NAFLD treatment has been investigated. Clinical meta-analyses have shown that resveratrol intake ameliorated NAFLD primarily through AMPK/SIRT1 and anti-inflammatory pathways [112]. The GLP-1 receptor agonist semaglutide improves several pathological characteristics of NAFLD, including reduced steatosis, lobular inflammation, hepatocellular ballooning, and alleviation of NASH progression Emerging evidence suggests the therapeutic potential of correcting dysregulated epigenetic modifications in NAFLD.…”
Section: Therapeutic Interventionmentioning
confidence: 99%